\( \begin{array}{lll}\text { (a) } \frac{16^{2} \cdot\left(3^{2}\right)^{4}}{2^{7} \cdot 2^{5} \cdot 81} & \text { (b) } \quad \frac{\left(2^{x}\right)^{4} \cdot 9^{x}}{12^{2 x}} & \text { (c) } \frac{16^{x-1}}{2^{4 x} \cdot 32}\end{array} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To tackle each of these mathematical expressions that involve exponents and simplification, let's dive into the numbers and their adjustments. For part (a), we can first simplify the numerator and denominator: The numerator \(16^2 \cdot (3^2)^4\) becomes \( (2^4)^2 \cdot (3^2)^4 = 2^8 \cdot 3^8 \). The denominator \(2^7 \cdot 2^5 \cdot 81\) uses \(81=3^4\), so it becomes \(2^{7+5} \cdot 3^4 = 2^{12} \cdot 3^4\). Bringing it all together, we have: \[ \frac{2^8 \cdot 3^8}{2^{12} \cdot 3^4} = \frac{3^{8-4}}{2^{12-8}} = \frac{3^4}{2^4} = \left(\frac{3}{2}\right)^4 = \frac{81}{16} \] For part (b), we start simplifying: The expression \((2^x)^4 \cdot 9^x\) can be rewritten as \(2^{4x} \cdot (3^2)^x = 2^{4x} \cdot 3^{2x}\) and the denominator \(12^{2x}\) can be expressed as \((2^2 \cdot 3)^{2x} = 2^{4x} \cdot 3^{2x}\). Thus, we get: \[ \frac{2^{4x} \cdot 3^{2x}}{2^{4x} \cdot 3^{2x}} = 1 \] For part (c), we rewrite \(16^{x-1}\) as \(2^{4(x-1)} = 2^{4x-4}\) and \(32\) as \(2^5\). Now we have: \[ \frac{2^{4x-4}}{2^{4x} \cdot 2^5} = \frac{2^{4x-4}}{2^{4x+5}} = \frac{1}{2^{4x + 5 - (4x - 4)}} = \frac{1}{2^1} = \frac{1}{2} \]